Legal Basis of the Ban of Mobbing in the foreign Countries - Гаращенко, Людмила Петрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article examines legislation of such countries as Norway, Sweden, France, Germany, Italy on prohibiting mobbing (psychological pressure) in the workplace. The main feature of the legislature of the countries surveyed is to defence of workers’ dignity, prevention and protection from stress and psychological pressure. It should be noted that in Europe, great importance is given to the problems of mobbing, because any person spends much time exactly at work. Therefore, any permanent psychological terror, emotional stress, harassment in the workplace, even for a short period of time imprint negatively on the human psyche, and during prolonged exposure change into real physical diseases and can end tragically. In 1998, the ILO set mobbing on the grade along with rape and murder, that highlights the devastating and negative consequences of mobbing for a human once more. The current legislative framework aims mainly to ban mobbing in the workplace, and the employer’s liability concerning compensation to the employee for damages. It is necessary to study experience of European countries and use it in Ukraine to improve the employees’ conditions of work, including through the creation of comfortable psychological atmosphere and protection of the worker’s dignity.